Prognostic and predictive value of estrogen receptor 1 expression in completely resected non‐small cell lung cancer. Issue 8 (7th May 2013) - Brueckl, Wolfgang Michael; Al‐Batran, Salah‐Eddin; Ficker, Joachim Hans; Claas, Silke; Atmaca, Akin; Hartmann, Arndt; Rieker, Ralf Joachim; Wirtz, Ralph Markus
<x xml:space="preserve">Abstract</x> Adjuvant chemotherapy (ACT) leads to a modest improvement in survival among patients with completely resected non‐small cell lung cancer (NSCLC) but molecular predictors are still rare. Publicly available gene microarray, clinical and follow‐up data from two different studies on early‐stage NSCLC were used to determine the expression of estrogen receptor 1 (ESR1). Expression values were calculated against clinical and survival data in a training set (n = 138) and a test set (subpopulation from the adjuvant JBR.10 study) allowing the determination of the prognostic effect of ESR1 in the observational arm as well as the predictive effect of ESR1 regarding ACT. Data were well balanced in terms of ESR1 expression. ESR1 high expression was of significant positive prognostic value in the training set and this could be confirmed in the test set cohort (hazard ratio for overall survival 0.248, 95% confidence interval: 0.088–0.701; p = 0.008). Additionally, ESR1 low tumors showed a benefit from ACT in terms of 5‐year survival (33.3% observation arm and 77.8% ACT arm; p = 0.003), whereas patients with ESR1 high tumors did not have any benefit from ACT (test of interaction p = 0.024). ESR1 is an independent positive prognostic factor for survival in early‐stage NSCLC patients. Patients with ESR1 high tumors did not benefit from ACT.